Kelayakan Limbah Karung Goni sebagai Bahan Dasar Pembuatan Hiasan Kepala (Headpiece) - Nesya Dinda Sabilla; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the suitability of burlap sack waste as a raw material for headpieces. This study used a quantitative descriptive approach with a one-shot case study model to test the product's suitability. The assessment process was conducted in two stages: a product validity test by three expert panelists and a preference test by 20 moderately trained panelists. The validity test aimed to assess the product's technical aspects, including shape, neatness, strength, color, and finish. The validity test results showed an average score of 93%, categorized as "very valid." The preference test was conducted to determine the level of user acceptance of the product based on aspects of shape, strength, aesthetics, neatness, ease of application, and finish, with an average score of 88%, categorized as "very like." Based on these findings, burlap sack waste was deemed suitable for use as a raw material for headpieces because it meets quality standards, has visual appeal, and has the potential to be developed into an economically valuable and environmentally friendly product.